Complete Genome Sequencing and Comparative Genome Characterization of Lactobacillus johnsonii ZLJ010, a Potential Probiotic With Health-Promoting Properties - Zhang, Wei; Wang, Jing; Zhang, Dongyan; Liu, Hui; Wang, Sixin; Wang, Yamin; Ji, Haifeng (Frontiers in Genetics, 2019)
Lactobacillus johnsonii ZLJ010 is a probiotic strain isolated from the feces of a healthy sow and has putative health-promoting properties. To determine the molecular basis underlying the probiotic potential of ZLJ010 and the genes involved in the same, complete genome sequencing and comparative genome analysis with L. johnsonii ZLJ010 were performed. From among the 1,959 protein-coding sequences, genes known to confer probiotic properties were identified, including genes related to stress adaptation, biosynthesis, metabolism, transport of amino acid, secretion, and the defense machinery. ZLJ010 lacked complete or partial biosynthetic pathways for amino acids but was predicted to compensate for this with an enhanced transport system and some unique amino acid permeases and peptidasesthat allow it to acquire amino acids and other precursors exogenously. The comparative genomic analysis of L. johnsonii ZLP001 and seven other available L. johnsonii strains, revealed 2,732 pan-genome orthologous gene clusters and 1,324 core-genome orthologous gene clusters. Phylogenomic analysis based on 1,288 single copy genes showed that ZLJ010 had a closer relationship with the BS15 from yogurt and DPC6026 from the porcine intestinal tract, but was located on a relatively standalone branch. The number of clusters of unique, strain-specific genes ranged from 42 to 185. A total of unique 219 unique genes present in the genome of L. johnsonii ZLJ010 primarily encoded proteins that are putatively involved in replication, recombination and repair, defense mechanisms, transcription, amino acid transport and metabolism, and carbohydrate transport and metabolism. Two unique prophages were predicted in the ZLJ010 genome.